2017
DOI: 10.1111/nyas.13405
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin protects against intestinal inflammation and bacteria‐induced barrier dysfunction in vitro

Abstract: The iron-binding glycoprotein lactoferrin (LF) is naturally present in human breast milk. Several studies suggest that LF contributes to infant health and development owing to a variety of protective effects, including antimicrobial and anti-inflammatory features. Therefore, we aimed to elucidate its protective properties on intestinal epithelial barrier dysfunction induced by infection or inflammation using the human epithelial cell culture models HT-29/B6 and T84. During barrier perturbation induced by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…In addition, indole-3-propionic acid (IPA) had positive effects on fructose metabolism (Jennis et al, 2018 ). Additionally, T84 cells have been utilized to study protective effects of Lactoferrin on bacterial-induced barrier dysfunction showing that Lactoferrin maintains tight junction structure during Yersinia enterocolitica infection (Hering et al, 2017 ).…”
Section: Intestinal Host Models For Microbiome Researchmentioning
confidence: 99%
“…In addition, indole-3-propionic acid (IPA) had positive effects on fructose metabolism (Jennis et al, 2018 ). Additionally, T84 cells have been utilized to study protective effects of Lactoferrin on bacterial-induced barrier dysfunction showing that Lactoferrin maintains tight junction structure during Yersinia enterocolitica infection (Hering et al, 2017 ).…”
Section: Intestinal Host Models For Microbiome Researchmentioning
confidence: 99%
“…Taken orally, it has been shown that approximately 60-70% of lactoferrin survives gastric hydrolysis 20 to enter the intestine, with likely higher ability to tolerate the stomach in neonates due to lower levels of gastric acidity 21 . Numerous clinical studies indirectly suggest a more generalized capacity of lactoferrin to reinforce the body's epithelial barriers, such as a capacity to decrease incidence of necrotizing enterocolitis (NEC) in premature infants 22 , decrease days and severity of diarrheal illness [23][24][25] , and protect against upper respiratory tract infection 23 . In addition, lactoferrin has demonstrated the capacity to protect from methotrexate induced barrier dysfunction in rats 26 .…”
Section: Development and Broad Administration Of New Therapeutics Capmentioning
confidence: 99%
“…Moreover, milk provokes a TGF-β response in gingival fibroblasts 20 . Milk is also a rich source of lactoperoxidase 21 , lactoferrin 22 and osteopontin 23 , all causing cellular responses. These findings have prompted us to determine the reaction of oral squamous cell carcinoma cells to milk using molecular screening approaches.…”
mentioning
confidence: 99%